The disappearing male - Lachkar, Joan (Jason Aronson, 2013)
This book provides a psychoanalytic/psychodynamic description of eight different kinds of men who disappear from relationships without warning or explanation. The term is not restricted to merely a physical disappearance but also to ones who emotionally disappear such as the Robotic Man described in the chapter of the OCD. Lachkar's personal, clinical, and professional experience have shown a number of women who have been vastly confused and hurt by the disappearing male. These men appear to be madly in love at the onset and then suddenly vanish without an explanation. Many of these women come into therapy sessions depressed, feeling traumatized, and abused by men who promise them the world, act as though they are the love of their lives, and then suddenly vanish without a call. By acknowledging the diagnostic distinctions of eight different types of disappearing men, this book can help to assist these women in recognizing the red flags and danger signs to prevent them from faltering in their relationship efforts. The Disappearing Male describes the symptoms of eight different diagnostic types of men that women frequently encounter. The symptoms and dynamics that are outlined in this book will vastly enhance an individual's capacity to become aware of the disappearing male syndrome. This book is significant to the awareness and self-esteem of women in relationships, the dating world, and to the therapists that treat them.